Find the slope perpendicular to 2x+3=4y

mikioneliir 2022-09-23 Answered
Find the slope perpendicular to 2x+3=4y
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Ryan Underwood
Answered 2022-09-24 Author has 4 answers
Since the given equation is a simple linear equation, it's not difficult to find the slope perpendicular to the given equation.
Now, we know that the product of the value of the slopes of 2 perpendicular lines is equal to negative of unity, that is
m 1 m 2 = - 1
The above equation should first be made into a general slope equation first, so it becomes
2 ( x + 3 2 ) = 4 y y = 1 2 ( x + 3 2 )
So the slope of the above given equation is taken as m 1 = 1 2
Now, substituting this in the given equation, we get m 2 1 2 = - 1 m 2 = - 2
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-06-01

Find the linear approximation of the function f(x)=4x at a=0
Use L(x) to approximate the numbers 3.9 and 3.99 Round to four decimal places

asked 2022-11-04
Find the point-slope form of the equation of the line passing through the point (10,-9);m=-2
asked 2022-09-03
Find the equation of the line perpendicular to y = - 7 15 that passes through (−25,5)
asked 2022-11-10
Find the slope of a line parallel to y=5−2x
asked 2022-07-01
I am studying Helgason's Differential Geometry and Symmetric Spaces, trying to understand real forms of Lie Algebras.
My problem is related to Lemma 6.1 (1st edition):
Let K 0 be the Killing form of a Lie algebra g over R , and K the Killing form of the complexification Lie algebra g C . Then
K 0 ( X , Y ) = K ( X , Y )     X , Y g

My problem:
Understanding the previous equation as K ( X , Y ) K ( X + i 0 , Y + i 0 ) I would get twice the result stated in the book. This is due to the following facts.
1. ad C ( X ) End C ( g C ), acting as
ad C ( X ) [ A + i B ] = [ X + i 0 , A + i B ] C = [ X , A ] + i [ X , B ]
therefore I can write it as a direct sum of the real adjoint map
ad C ( X ) = ad ( X ) ad ( X )
2. Trace [ ad C ( X ) ad C ( Y ) ] = Trace [ ad ( X ) ad ( Y ) ad ( X ) ad ( Y ) ] = 2 Trace [ ad ( X ) ad ( Y ) ]

Background:
1. Helgason's definition of complexification: g C = g × g g g with the complex structure
J : ( X , Y ) X + i Y ( Y , X ) Y + i X
extending the Lie bracket by C -linearity:
[ X + i Y , Z + i T ] C = [ X , Z ] [ Y , T ] + i [ X , T ] + i [ Y , Z ]
2. Killing form of any Lie algebra over an arbitrary field K :
B ( X , Y ) = Trace [ ad ( X ) ad ( Y ) ]
where ad ( X ) is the K -linear map [ X , ].
asked 2022-11-10
Find a standard form equation for the line with (-1, 9) and is perpendicular to the line whose equation is x = 8
asked 2022-10-10
Find the smallest possible dimensions for the rectangle if the length of a rectangle is 4cm more than the width and perimeter is at least 48cm